The Transformational Leadership Behaviours of School Principals of Vocational High School in Palembang - Sadrah Ihsani; Rita Inderawati; Machdalena Vianty (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The aims of this study were to investigate the description of the transformational leadership behaviour of school principals of private vocational senior high schools in Palembang, and how the school principals implemented the transformational leadership in the school and how the transformational leadership impacted to the teacher performance. The subjects of this study was four school principals of four private vocational senior high schools in Palembang. The data collection was taken from the questionnaire and interview. The data from the questionnaire were analyzed by simple statistical analysis and the interview was analyzed by using thematic analysis. The findings showed that the description of transformational leadership demonstrated the four dimension of transformational leadership, such as idealized influence, inspirational motivation, intellectual stimulation and individual consideration. Later in this study it was found that school principals implement transformational leadership by using some ways such as building the trust, motivation, facilitation and communication. It is also found that the transformational leadership behavior of school principal of private vocational high school in Palembang has an impact to the teacher performance in teaching learning process.